Farmers’ Perceptions of the Efficacy of Current Climate Risk Adaptation and Mitigation Strategies on Agriculture in The Gambia - Sheriff Ceesay; Fatima Lambarraa-Lehnhardt; Mohamed Ben Omar Ndiaye; Diatou Thiaw; Mamma Sawaneh; Johannes Schuler (Land)
Agricultural systems face increasing challenges due to climate change, necessitating effective adaptation and mitigation strategies. This study investigates smallholder farmers’ perceptions of the efficacy of these strategies in The Gambia, employing a mixed-method approach that includes a perception index (PI), effectiveness score (ES), importance–performance analysis (IPA), and statistical analysis. A structured survey was conducted among 420 smallholder farmers across three agricultural regions. Farmers rated adaptation and mitigation strategies using a Likert scale, and a PI was developed to quantify their responses. The index was 0.66, indicating a moderate level of perceived effectiveness. Additionally, ES was calculated to assess the performance of various strategies, while IPA categorized strategies based on their adoption and perceived impact. Chi-square tests and factor analysis were applied to explore differences in perceptions. The findings reveal that strategies such as crop diversification, pesticide application, irrigation, and the use of inorganic fertilizers are widely adopted and perceived as effective. The IPA matrix identified key strategies needing improvement, particularly those with high importance but low performance. Barriers to adoption include limited financial resources (77%), lack of government support (64%), and insufficient knowledge (52%), with no significant gender-based differences in perceptions. This study underscores the need for policy interventions that integrate farmers’ perceptions to enhance climate resilience. Targeted investments in adaptive technologies, financial support, and knowledge-sharing platforms can improve adoption and effectiveness. This research provides valuable insights into the interplay between farmer perceptions, adaptation strategies, and agricultural sustainability in The Gambia.